Electronic combination lock door system - Mohamad Nasir, Ahmad Faisal; Malek, Muhamad Zubair (2016)
The basic requirement of security can be achieved by designing electrical or mechanical locks that are designed using a key, but a lot of keys are required to lock a big area. Moreover, the used of traditional locks are heavy and not protective where it can be broken down easily by using some tools. Therefore, this keyless door project is designed to facilitated consumer and their house is more secure from any home burglary. This project used a microcontroller as a control unit that has been programmed. The program is writing in mikroC software and testing it in Proteus software to ensure the circuit performances achieved the project objective before prototyping process is performs. PIC microcontroller is used to make it low cost compared to the other microcontroller. This project is suitable for all levels o f income because the project is cheaper compared to similar projects that are on the market now. Furthermore, it used a code that entered through keypad to make it more flexible to security system. It provides users with an efficient and reliable security system that supports the use of an electronic keypad arranged to send signals to the control unit which is PICI6F887 microcontroller. This control unit either activates the port to which the green LED and motor driver is connected when the correct password is entered or activates the port to which the red LED and buzzer alarm is connected when the wrong Password is entered. Overall design and implementation of the prototype is fully functional and user friendly. The perfect project prototype was placed outside the door and ready to be use.